Exploration of permeability and antifouling performance on modified cellulose acetate ultrafiltration membrane with cellulose nanocrystals. (15th October 2017) - Lv, Jinling; Zhang, Guoquan; Zhang, Hanmin; Yang, Fenglin
Highlights: The CNCs were introduced into CDA matrix to prepare ultrafiltration membrane. The CNCs/CDA membrane possessed high porosity, hydrophilicity and large pore size. The CNCs/CDA membrane had excellent permeability and antifouling property. The CNCs/CDA membrane exhibited a better stability for recycling utilization. Abstract: Cellulose nanocrystals (CNCs) were introduced into cellulose diacetate (CDA) matrix via immerged phase-inversion process, aiming to improve the filtration and antifouling performance of CNCs/CDA blending membrane. The effects of CNCs on membrane morphologies, hydrophilicity, permeability and antifouling property were investigated. Results showed that the incorporation of CNCs into CDA membrane could effectively enhance the permeability and antifouling property of CNCs/CDA blending membrane by optimizing membrane microstructure and improving membrane hydrophilicity. A high pure water flux of 173.8 L/m 2 h was achieved for the CNCs/CDA blending membrane at 200 KPa, which is 24 times that of the CDA membrane (7.2 L/m 2 h). The bovine serum albumin (BSA) adsorption amount of the CNCs/CDA blending membrane decreased about 48% compared to that of the CDA membrane. Additionally, the CNCs/CDA blending membrane exhibited better antifouling performance with the flux recovery ratio ( FRR ) of 89.5% after three fouling cycles, compared to 59.7% for the CDA membrane.